PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA INGGRIS DASAR BERBASIS ANDROID UNTUK KELAS V SEKOLAH DASAR - Sang Ayu Made Krisna Dewi Natalia; I Ketut Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2020)
This research aimed to produce an English learning media based on Android for grade V of elementary school students. This research belongs to Research and Development. In its implementation, this research has two steps such as pre-production and production. In the pre-production consists of planning, idea concept, research/visual analysis, designing menu plot, and asset making. In the next step that is production consists of arranging asset, adding action script for navigation of the media, and rendering the media. The result of this research is a learning media based on Android that later can be used in the English learning process in the classroom. The materials chosen in this media are in the form of basic materials for English, those are the introduction of Noun, Verb, and Adjective. In the Menu plot, first started with Intro, then enter the Menu Page, where in Menu Page there are three choices, those are Verb, Noun, and Adjective materials. From each material, there are nine examples of pictures for each category based on topic. This learning media based on Android will become an effective media that can be used in the learning process that later make the learning process become interactive, interesting, and a lot of fun. The next development is by doing affectivity test for the existing media. This affectivity test is done for the next media development.